Mauthner versus Wittgenstein - Barroso, Paulo (2016)
Mauthner esteemed language as a philosophical inquiry. He measured the philosophical entailments between language and reality and the consequent knowledge produced by such entailments. He questioned language’s aptitude to express and represent reality and, according to him, language is a critical source of knowledge and an unfaithful representation of reality, because there is a gap between language and reality, i.e. language distorts perception and engenders false and fictitious assumptions about reality. Language fosters superstition, creates gods and idols and exerts a dominating power over the intellect. Mauthner pointed out a critique of language based on metaphors, which would serve to address and clarify the deformation of reality. Wittgenstein, unlike himself suggested, was inspired by Mauthner. Both showed interest toward the critical analysis of language and there are many conceptual similarities between their language’s conceptions (e.g. concerning the use of metaphors to understand language). Therefore, this paper seeks a) to emphasize Mauthner’s metaphors on language as an accurate interpretation regarding the philosophical entailments between language and reality, and b) to demonstrate the epistemological legacy of Mauthner’s critique of language to Wittgenstein’s philosophy of language.